Comparative Study on E-Government Implementation: Lessons from Developed and Developing Countries - Amaliah, Wafiq Azizah Reski; Haliah, Haliah; Nirwana, Nirwana (Dinasti International Journal of Management Science, 2025)
This study uses a Systematic Literature Review (SLR) approach to compare e-government implementation in developed and developing countries based on 2014-2025 literature. The findigs show that developed countries excel in digital infrastructure maturity, integrated policies, use-centric services, and strong data protection. In contrast, developing countries continue to face various challenges. The success of e-government is not only determined by technology, but also institutions, digital leadership, and public participation. This study recommends the formulation of an inclusive national e-government strategy, strengthening regulations, and public engagement as the key to effective and sustainable public sector digital transformation.